Ni Luh Djelantik’s Political Campaign Strategy in the 2024 Bali Regional Representative Council Election - Putra, Alvino Joshua Lallo; Nurak, Anastacia Patricia Novlina; Noerasto, Toto (Bali Membangun Bali: Jurnal Bappeda Litbang, 2025)
Purpose: This research was conducted to determine the political campaign strategy used by Ni Luh Putu Ary Pertami Djelantik in winning votes in the 2024 Regional Representative Council (Dewan Perwakilan Daerah/DPD) Legislative Election. Research method: This research uses a qualitative approach by collecting data through observation, interviews and documentation. With a sample size of 3 (three) people. The data analysis technique uses an interactive analysis. Results and discussion: The political campaign strategy implemented by Ni Luh Putu Ary Pertami Djelantik includes an emotional approach to voters, emphasis on social issues especially in Bali, creating a simple image, and highlighting herself as the only female candidate in the DPD legislative election Bali 2024. She succeeded in implementing an effective campaign strategy in the 2024 Bali DPD legislative election. Implication: Her approach included strengthening his image through the role of a "mamak" who is close to the community, using social media to strengthen personal branding, focusing on issues of women's empowerment, and paying attention to social and humanitarian problems.